Serotyping of toxoplasma gondii: striking homogeneous pattern between symptomatic and asymptomatic infections within Europe and South America (2008)
Field isolates of Toxoplasma gondii in Europe and North America have been grouped into three clonal lineages that display different virulence in mice. Whether the genetic structure of the parasite is related to clinical expression in humans has not yet been demonstrated. We developed an enzyme-linked immunosorbent assay which uses lineage-specific, polymorphic polypeptides derived from the dense granule antigens, GRA5 and GRA6. Our goal was to compare serotypical patterns observed in asymptomatic versus symptomatic (ocular disease and severe infection in human immunodeficiency virus (HIV)-positive patients) infections among patients from Europe and South America. Independent of the clinical presentation of the disease, serotypes differed according to geographical origin, with a homogeneous distribution of serotype II in Europe and of serotypes I and III in South America. We conclude that GRA5–GRA6 serotyping is an interesting tool to study serotype prevalence in populations but it is not an accurate marker of pathogenicity of Toxoplasma infection in humans.